Limitations of the social relationships domain of WHOQOL-Bref - Patrício, Brígida (2012)
The aim of this study is to assess the suitability of the social relationships (SR) domain of the WHOQOL-Bref by comparing it with the WHOQOL-100 SR domain. SR are an essential consideration in clinical rehabilitation after stroke, and especially for those who have aphasia (language impairment).